"The working language is Norwegian. Not that this means anything, it seems": when expectations meet the new multilingual reality. (2nd January 2021) - Hiss, Florian; Loppacher, Anna
ABSTRACT: Linguistic and cultural diversity in Northern Norwegian working life has increased dramatically in the twenty-first century. Based on a series of telephone interviews with company representatives, this article presents an overview of the new multilingual reality in many workplaces and analyzes how managers and administrators position their expectations and experiences of it. Participants' responses suggest that many workplaces are linguistically segregated. Though most participants said their companies did not have explicit workplace language policies, they expressed clear perceptions of how things should be in their workplaces, and these were often in conflict with their descriptions of the status quo. We also show how multiple contextual conditions in and out of workplaces, both ideological and practical, informed participants' accounts of multilingual practices in their workplaces. Static and normative ideological positions are challenged by employees' language choices, practices, and developments on a societal level, particularly those of the labour market, which regulates companies' access to workers. Our study reveals the need for applicable knowledge about multilingual practices and sociolinguistic relations in workplaces.